Affinity sorption analysis of the structure of poly(G)·poly(C) complex obtained by means of template-dependent synthesis - Surzhik, M.A.; Timkovsky, A.L. (Биополимеры и клетка, 1993)
The analysis of the structure of poly(G)·poly (C) complexes obtained by the enzymatic synthesis on poly(C) template was carried out using the method of affinity sorption. This latter was used also for the purification of the synthesized so far complexes from the redundant template as well as for the investigation of the structure of poly(G) ·poly(C) complexes obtained by the «traditional» mixing of complementary homopo-lynucleotides. It was shown that the degree of template transcription depends on the quality of RNA polymerase and the incompleted transcription is connected with the inhibition of the elongation of poly(G) chain. Проведено аналіз структури комплексів полі(Г)·полі(Ц), одержаних ферментативним синтезом на матриці полі (Ц), за допомогою афінної сорбції. Останню застосовано також для очищення препаратів таких комплексів від надміру невикористаної матриці, а також для дослідження структури комплексів полі(Г)·полі(Ц), виділених традиційним методом змішування розчинів комплементарних полінуклеотидів. Показано, що повнота прочитання матриці полі(Ц) залежить від якості РНК-полімерази, а неповне прочитання пов’язане з пригніченням елонгації нитки полі (Г), яка по ній синтезується. Проведен анализ структуры комплексов поли (Г) · поли (Ц), полученных ферментативным синтезом на матрице поли (Ц), с помощью аффинной сорбции. Последняя применена для очистки препаратов таких комплексов от избытка неиспользованной матрицы, а также для исследования структуры комплексов поли (Г) · поли (Ц), выделенных традиционным методом смешивания растворов комплементарных полинуклеотидов. Показано, что полнота прочтения матрицы поли (Ц) зависит от качества РНК-полимеразы, а неполное прочтение связано с угнетением элонгации нити поли (Г), которая по ней синтезируется.